Effects of diflubenzuron and mancozeb on soil microarthropods: a long-term study - Adamski, Zbigniew; Błoszyk, Jerzy; Piosik, Katarzyna; Tomczak, Kamila (Biological Letters, 2010)
Soil microarthropods exposed to the pesticides mancozeb (240 mg per 1 m2) or diflubenzuron (7.2 mg of diflubenzuron per 1 m2) were studied for 6 months after a single application. The observed taxa included Collembola, Insecta, Myriapoda, and 4 groups of mites: Actinedida (=Prostigmata), Gamasina, Uropodina, and Oribatida. Their abundance in soil was subject to seasonal fluctuations, but for a majority of taxa no significant differences were noticed between the control and exposed plots. The total number of microarthropods was insignificantly lower in exposed groups. Myriapods were the only taxon that was close to extinction after a single exposure to diflubenzuron. These data prove that soil has some buffering capacity, and this fact should always be taken into consideration when estimating the risk for the environment. However, the situation may change if the application of pesticides is repeated.